PENGARUH RELIGIUSITAS DAN RELIGIOUS COPING TERHADAP MORALITAS REMAJA - Novelia Novelia; Hadi Candra; Eko Sujadi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Adolescents, a demographic prone to challenging prevailing norms, often navigate a complex identity search process leading to the exploration of behaviors conflicting with established moral standards. This study investigates the impact of religiosity and religious coping on morality. Employing a survey design, 128 adolescents in Sungai Penuh city, Jambi Province, were selected through convenience sampling. Researchers utilized the Morality Scale, Religiosity Among Muslim Scale, and Brief RCOPE for data collection, analyzing results through simple and multiple linear regression techniques. Findings suggest that adolescent morality falls within the moderate range, while religiosity and religious coping score high. The study underscores the influence of religiosity and religious coping on adolescent morality emphasizing the significance of enhancing these factors to address low morality levels among adolescents through targeted prevention and intervention